Micropropagation of pineapple (Ananas Comosus) cv. Smooth cayenne and Moris / Abdelhamid M. Hamad - Hamad, Abdelhamid M. (2009)
A total of 25 experiments were conducted to test the effect of several factors such as hormone types and concentrations, incubation periods, subcultures, medium states, sucrose, pH, explants size, explants density and medium volume per culture and medium strength on the shoot formation per explant, total shoots, total cost and cost per shoot of Smooth cayenne and Moris pineapple at each and over 4 consecutive subcultures. Rooting responses and plantlets quality of both cultivars were tested in different hormones, media strength, shoots age, sucrose content and incubation periods. Survival during acclimatization was evaluated in relation to rooting treatments, plantlet quality, substrate types and mixing ratio under polyethylene enclosure. Two protocols of low cost and simplicity were developed for commercial propagation of Smooth cayenne and Moris pineapple. The procedure involved aseptic culture of shoot tips explants excised from crown of Smooth cayenne and shoots of field grown Moris plants followed by shoot multiplication, rooting and acclimatization. A total of 121,125 planting materials of Smooth cayenne could be produced per year from single shoot at cost of 26 cents per propagule. Single shoot per culture underwent 4 multiplication cycles each 75 days long on 20 ml of agar solidified full strength MS enriched with sucrose at 30 g/l, combination of BAP at 3.25 and IAA at 1.75 mg/l and pH adjusted to 5.7. The total shoots, total cost and cost per shoot at the first and after 2, 3 and 4 subcultures were 17; 323; 8,075 and 12,1125 shoots, RM 1.61; RM 28.63; RM 542.82 and RM 13,437.36 and 6.5; 6.2; 4.7 and 7.8 cents respectively. Similarly, a total of 15,120 planting materials of Moris per year could be produced starting with 12 shoots at cost of 23 cents per propagule. Shoots were cultured at density of 4 shoots per culture and underwent 4 multiplication cycles each 60 days long on 8 ml of liquid full strength MS enriched with sucrose at 20 g/l, BAP at 2.0 mg/l and pH VII adjusted to 5.0. The total shoots, total cost and cost per shoot at the first and after 2, 3 and 4 subcultures were 84; 504; 3,024 and 15,120 shoots, RM 2.98; RM 21.96; RM 134.26 and RM 806.51 and 4; 4; 4 and 5 cents respectively. The shoots of both cultivars were rooted at density of 5 shoots per culture in 6 ml of quarter strength liquid MS enriched with sucrose at 20 g/l, but different hormones. NAA at 1.0 mg/l was used for rooting of Smooth cayenne and IBA at 2.0 mg/l for rooting of Moris, pH adjusted to 5.0 and the cultures incubated for 30 days. The plantlets of both cultivars were acclimatized (> 84 %) in pots filled with sands, enclosed with polyethylene sheet for 15 days and kept under shade house for 75 days. The cost of rooting was estimated as 13 cents per shoot and that of acclimatization was 5 cents per plantlet. The production capacity can be increased to any level, preferably by increasing the starting explants material.